2013
DOI: 10.1021/ja4042077
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Patterned Graphene Surfaces by a Force-Accelerated Diels–Alder Reaction

Abstract: Cyclopentadienes (CPs) with Raman and electrochemically active tags were patterned covalently onto graphene surfaces using force-accelerated Diels-Alder (DA) reactions that were induced by an array of elastomeric tips mounted onto the piezoelectric actuators of an atomic force microscope. These force-accelerated cycloadditions are a feasible route to locally alter the chemical composition of graphene defects and edge sites under ambient atmosphere and temperature over large areas (∼1 cm(2)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
132
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 30 publications
1
132
0
1
Order By: Relevance
“…50 It was found that graphene models are more stable as open-shell singlet states than as closed-shell singlet and open-shell triplet states. 51 For this purpose, all calculations reported here were performed using Gaussian 09 (see details in the ESI ‡) using the (U) M06-2X level of theory 52,53 and 6-31G(d) basis set [54][55][56][57][58] as this method is reported to provide excellent energy values for cycloaddition reactions. 59 This approach therefore takes into account the dispersion interactions because the sp 2 framework of graphene can interact through p-stacking and CH-p interactions with the dipolarophile.…”
Section: Theoretical Studymentioning
confidence: 99%
“…50 It was found that graphene models are more stable as open-shell singlet states than as closed-shell singlet and open-shell triplet states. 51 For this purpose, all calculations reported here were performed using Gaussian 09 (see details in the ESI ‡) using the (U) M06-2X level of theory 52,53 and 6-31G(d) basis set [54][55][56][57][58] as this method is reported to provide excellent energy values for cycloaddition reactions. 59 This approach therefore takes into account the dispersion interactions because the sp 2 framework of graphene can interact through p-stacking and CH-p interactions with the dipolarophile.…”
Section: Theoretical Studymentioning
confidence: 99%
“…图式 11 1,3-环戊二烯与单线态氧气的反应 Scheme 11 Reaction of 1,3-cyclopentadiene with singlet oxygen 环戊二烯的 Diels-Alder 反应的高反应活性使其在 有机合成 [69] 、生物分子固定化、热敏聚合物和功能性材 料等方面具有广泛的应用 [70,71] . 2015 年, Levandowski…”
Section: 烯炔反应法unclassified
“…[7][8][9][10] For example, Haddon and co-workerss howed that graphite/graphenec an serve as a diene by reacting with tetracyanoethylene (TCNE) at room temperature. [7][8][9][10] For example, Haddon and co-workerss howed that graphite/graphenec an serve as a diene by reacting with tetracyanoethylene (TCNE) at room temperature.…”
Section: Introductionmentioning
confidence: 99%